Cascadable Current-Mode First-Order All-Pass Filter Based on Minimal Components. (17th June 2013) - Mohan, Jitendra; Maheshwari, Sudhanshu
Abstract : A novel current-mode first-order all-pass filter with low input and high output impedance feature is presented. The circuit realization employs a single dual-X-second-generation current conveyor, one grounded capacitor, and one grounded resistor, which is a minimum component realization. The theoretical results are verified using PSPICE simulation program with TSMC 0.35  μ m CMOS process parameters.